The Influence of Gamification Affordance on Customer Loyalty among E-Commerce in Indonesia - Zega, Luther Risman Luosaro; Perdanakusuma, Andi Reza; Hariyanti, Uun (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: The e-commerce industry in Indonesia is experiencing competition due to the rising number of users and price-sensitive consumers, making user loyalty a major challenge for companies. Although gamification, such as task/quest type, was recognized as a strategy to boost loyalty, previous studies showed inconsistent results regarding its impact on hedonic and utilitarian values.  Objective: This study aimed to explore the relationships among task/quest-type gamification affordance (GA), hedonic value (HV), utilitarian value (UV), satisfaction (SA), and loyalty (LOY) among Indonesian e-commerce users.   Methods: A total of 284 e-commerce app users who had engaged in task/quest-type gamification were selected as participants using a convenience sampling method. A quantitative method was adopted and survey data were examined by covariance-based structural equation modeling (CB-SEM) conducted in SmartPLS4.  Results: The analysis showed that gamification affordance significantly impacted users’ perceived hedonic and utilitarian values. An increase in these values significantly enhanced user satisfaction, and strongly correlated with loyalty. Gamification affordance also indirectly influenced loyalty through hedonic value, utilitarian value, and satisfaction.  Conclusion: Task/quest-type gamification affordance effectively enhanced user loyalty in Indonesian e-commerce by improving perceived hedonic and utilitarian values and satisfaction. These results suggested that gamification strategies focusing on task/quest-type elements could foster loyalty in a competitive e-commerce environment.  Keywords: Gamification Affordance, Hedonic Value, Utilitarian Value, Satisfaction, Loyalty